STRUKTUR KAWASAN MANGROVE DI KOLAGANA KOTA BAUBAU, SULAWESI TENGGARA - Waode Sitti Cahyani; Abdul Hadi Bone; Bahtiar Hamar; Ridwan Hasan (Journal of Aceh Aquatic Sciences, 2022)
Mangroves have important ecological and economic functions for nature and humans.Mangrove forest on the coast of Kolagana is one area that provides various benefits to support life for marine life and local communities. But on the other side, the structure and composition of mangroves have not been identified properly. So it is necessary to overcome the area so that the ecological function of the associated ecosystem around it remains sustainable. This study aims to examine the structure and composition of mangrove species on the coast of Kolagana, Baubau City. The results of the study are expected to provide information to stakeholders regarding the types of mangroves found in the research location. Mangrove forest zoning at the research site is dominated by 2 types of mangroves. Zone adjacent to the seadominated by the species Sonnetaria alba, while the inside part zone is dominated by Rhizophora apiculata.